CAMPUR KODE DALAM TUTURAN MASYARAKAT ETNIK CINA BENTENG DI DESA LEBAK WANGI, TANGERANG: KAJIAN SOSIOLINGUISTIK - Eva Oktaviany; A. Erna Rochiyati S.; Edy Hariyadi; Andang Subaharianto; Ali Badrudin (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2023)
The Benteng Chinese ethnic community in Desa Lebak Wangi, Tangerang uses Benteng Chinese dialect of Indonesian which is mixed with elements of Hokkian dialect of Chinese, English, Sundanese, and Betawi language. The purpose of this study is to describe the forms and factors behind the occurrence of code mixing in daily communication in the speech of Benteng Chinese ethnic community in Desa Lebak Wangi, Tangerang. This research uses a descriptive qualitative method. The results obtained from the data analysis show that the code mix in this study consists of two forms, namely: (1) code mix in the form of words; and (2) code mix in the form of phrases. Code mix in the form of words includes: (1) basic words; (2) affixed words; and (2) repeated words. The factors behind the code mix consist of three factors, namely: (1) role identification factor; (2) variety identification factor; and (3) desire to explain/interpret factor. Among the four code-mix entries in this study, Sundanese was the most common. The inclusion of Hokkian dialect of Chinese occurs when talking about family relationships, numerals, religious celebrations, and rituals. The inclusion of Sundanese elements occurs when communicating with family and neighbors to describe an activity, indicate a condition, and mention affirming affixes. The inclusion of Betawi language elements occurs when communicating with family and neighbors to emphasize or show something with high intonation. The inclusion of English elements occurs when young people mention the use of words on the internet or social media.